Positive Systems Theory and Applications (POSTA 2018) - Lam, James; Chen, Yun.; Liu, Xingwen; Zhao, Xudong; Zhang, Junfeng; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents high-quality original contributions on positive systems, including those with positivity in compartmental switched systems, Markovian jump systems, Boolean networks, interval observer design, fault detection, and delay systems. It comprises a selection of the best papers from POSTA 2018, the 6th International Conference on Positive Systems, which was held in Hangzhou, China, in August 2018. The POSTA conference series represents a targeted response to the growing need for research that reports on and critically discusses a wide range of topics concerning the theory and applications of positive systems. The book offers valuable insights for researchers in applied mathematics, control theory and their applications.
Ccompartmental Switched Systems -- Markovian Jump Systems -- Boolean Networks -- Positive Delay Systems.
Keywords: Control engineering; System theory; Control theory; Computational intelligence; Control and Systems Theory; Systems Theory, Control; Computational Intelligence